Dosis de gallinaza sobre las características agronómicas y el rendimiento de forraje del pasto Panicum maximun cv. Tanzania en el suelo compactado por la ganadería en Zungarococha Iquitos, Perú - 2018 - Vallejos Perez, Javier Segundo (2018)
This research was carried out at the National University of the Peruvian Amazon in the Project Vaccines of the Faculty of Agronomy in the Fundo de Zungarococha, entitled “Dosage of chicken manure on the agronomic characteristics and forage yield of Pasto Panicum maximun cv. Tanzania on soil compacted by livestock in Zugarococha Iquitos, Peru - 2018”. The evaluations were carried out at the eighth week after sowing with vegetative seed (bushes), in plots of 10 m x 2 m (20 m2) and an experimental area of 1248 m2. With a design of Complete Random Block Design (DBCA), with five treatments and four repetitions, the treatments under study were: T0 (0 tons of chicken / ha), T1 (10 tons of chicken / ha), T2 (20 tons of chicken / ha), T3 (30 tons of chicken / ha) and T4 (40 tons of chicken / ha), obtaining the following results: For agronomic characteristics, the T4 treatment (40 tons of chicken / ha), obtained The best result in height is 129.43 cm, Coverage Percentage of 92.30%, whole plant green matter of 3.13 kg / m2, dry matter of 0.69 kg / m2. The yield of green matter per hectare cut, you can reach 31,325.00 kilos / ha with the highest dose of chicken manure (T4).